Inhibition of P-glycoprotein expression and function by anti-diabetic drugs gliclazide, metformin, and pioglitazone in vitro and in situ - Mehran Mesgari Abbasi; Hadi Valizadeh; Hamed Hamishehkar; Parvin Zakeri-Milani (Wolters Kluwer Medknow Publications, 2016)
P-glycoprotein (P-gp) is a trans-membrane drug efflux pump. Several drugs are P-gp substrates. Some drugs may affect the activity of P-gp by inhibiting its function, resulting in significant drug-drug interactions (DDIs). It is critical to understand which drugs are inhibitors of P-gp so that adverse DDIs can be minimized or avoided. This study investigated the effects of gliclazide, metformin, and pioglitazone on the function and expression of P-gp. Rhodamine 123 (Rh 123) efflux assays in Caco-2 cells and western blot testing were used to study in vitro the effect of the drugs on P-gp function and expression. The in situ rat single-pass intestinal permeability model was developed to study the effect of the drugs on P-gp function. Digoxin and verapamil were used as a known substrate and inhibitor of P-gp, respectively. Digoxin levels in intestinal perfusion samples were analyzed by high-performance liquid chromatography. Intestinal effective permeability (Peff) of digoxin in the presence of 0.1, 10, and 500 μM gliclazide, 100 and 7000 μM metformin, and 50 and 300 μM pioglitazone was significantly increased relative to the digoxin treated cells (P < 0.01). P-gp expression was decreased by gliclazide, metformin and pioglitazone. Intracellular accumulation of Rh 123 by the drugs increased, but the differences were not significant relative to the control cells (P > 0.05). It was found that gliclazide, metformin, and pioglitazone inhibited P-gp efflux activity in situ and down-regulated P-gp expression in vitro. Further investigations are necessary to confirm the obtained results and to define the mechanism underlying P-gp inhibition by the drugs.